Strategi Pengembangan Bisnis UMKM Keripik Talas di Desa Lenteng Timur dengan Pendekatan Business Model Canvas - Noferdyan Firmansyah; Resti Destiarni (UPAJIWA DEWANTARA : Jurnal Ekonomi, Bisnis dan Manajemen Daulat Rakyat, 2026)
Taro-Chips MSMEs in East Lenteng Village are faced challenges and increasingly tight market competition due to increase in competitors in same field. Research results show that MSMEs of Talas-Chips are in quadrant I, which is supporting an aggressive strategy, meaning that MSMEs are in profitable position and support growth and new business model proposals have been proposed such as increasing partner relationships with other raw material suppliers. Apart from that, MSMEs carry out online marketing activities, add new variants, create attractive packaging, register business legality, and provide special bonuses to profitable customers. MSMEs can also expand consumer segments and develop key resources, such as social media, production machines, adding human resources in the production sector, and information technology. MSMEs also have to add social media accounts, add transportation costs, costs for promotions on social media, and use leftovers or pieces of cooked taro-chips to be repackaged in attractive packaging.